(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background- Sadness, feeling down, having a loss of interest or pleasure in daily activities - these are symptoms familiar to all of us. But, if they persist and affect our life substantially, it may be depression. Studies on the elderly population, either in the community, inpatient, outpatient and old age homes have shown that depression is the commonest mental illness in elderly subjects. Prevalence rate of major depression in India amongst the elderly was 31.2 per 1000. Objectives- 1) To determine the level of depression among elderly persons at selected old age home in Pune. 2) To determine the level of depression post intervention among elderly persons at selected old age home in Pune city. 3) To evaluate the effectiveness of mindfulness life intervention on the level of depression among elderly persons at selected old age home of Pune city. 4) To find the association between post-test depression level and selected demographic variables. Methodology A descriptive and a pre-experimental one group pre-test and post-test research design was adopted for this study. A non-probability purposive sampling technique was used to fetch a sample of 60. A modified geriatric depression scale (short form) was used to identify the depression in elderly persons of old age home. The reliability of Modified geriatric depression scale was found to be 0.92 by using Pearson’s co relation coefficient test. Results- out of 60 subjects, in pre-test, majority of 96.7% of the elderly persons from old age home had depression and 3.3% of them were normal. In post-test majority of 78.3% of the elderly persons from old age home had depression and 21.7% of them were normal. Average depression score in pre-test was 8.7 which reduced to 5.6 in post-test. T-value for this test was 10.6 with 59 degrees of freedom. Corresponding p-value was 0.000 which is small (less than 0.05). This indicates that depression of the elderly persons reduced remarkably after using mindfulness life intervention. Conclusion- This study concludes that mindfulness life interventions are effective in reducing depression of the elderly persons.